Structural similarity between thyroid peroxidase [Homo sapiens] and SARS-CoV-2 spike glycoprotein: An autoimmune thyroiditis triggering mechanism in COVID-19 carriers? - de Oliveira Andrade, Luis Jesuino; Correia Matos de Oliveira, Luisa; Vinhaes Bittencourt, Alcina Maria; Correia Matos de Oliveira, Gabriela (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: there are reports of autoimmune disease related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) such neurological syndromes and hematological syndromes, and more recently autoimmune thyroid dysfunctions have been described. These reports suggest that SARS-CoV-2 acts as a probable trigger for triggering the autoimmunity process. Aim: to evaluate structural similarity between thyroid peroxidase [Homo sapiens] (TPO) and SARS-CoV-2 spike glycoprotein (COVID-19), and to propose this similarity as a likely trigger for autoimmune thyroiditis. Methodology: using bioinformatics tools, we compare the amino acids (AA) sequences between protein structure of TPO and chain A COVID-19, chain B COVID-19, and chain C COVID-19, accessible in the National Center for Biotechnology Information database, by Basic Local Alignment Search Tool in order to locate the homologous regions between the sequences of AA. Results: the homology sequence between the TPO and COVID-19 ranged from 27.0 % (10 identical residues out of 37 AA in the sequence) to 56.0% (5 identical residues out of 9 AA in the sequence). The similar alignments demonstrated relatively high E values in function of short alignment. Conclusion: data suggest a possible pathological link between TPO and COVID-19. The structural similarity of AA sequences between TPO and COVID-19 may present a molecular mimicry suggesting the possibility of antigen crossover between TPO and COVID-19 that might represent an immunological basis for autoimmune thyroiditis associated with COVID-19.